Pharmacokinetics and Pharmacodynamics of Saruplase, an Unglycosylated Single-chain Urokinase-type Plasminogen Activator, in Patients with Acute Myocardial Infarction - Koster, Rudolph W; Cohen, Adam F; Hopkins, Gwyn R; Beier, Horst; Gunzler, Wolfgang A; van der Wouw, Poll A (Thrombosis and Haemostasis, 1994)
We examined in patients with acute myocardial infarction (AMI) the pharmacokinetics of saruplase, an unglycosylated, single chain, urokinase-type plasminogen activator (rscu-PA) by measuring urokinase-type plasminogen activator (u-PA) antigen and total u-PA activity, its conversion to active two-chain urokinase-type plasminogen activator (tcu-PA) and evaluated its effect on haemostatic parameters.Twelve patients were studied during and after administration of 20 mg bolus plus 60 mg continuous 1 h i.v. infusion of saruplase. For u-PA antigen and total u-PA activity (expressed as protein equivalents), where 234 U corresponds to 1 μg, respectively, steady state plasma concentrations were 2.75 ± 8.3 and 2.50 ± 7.0 μg/ml (mean ± standard deviation) and were reached within 20min, t1/2M was 9.1 ± 1.8 and 7.8 ± 1.3 min, t1/2λ2 1.2 ± 0.2 and 1.9 ± 0.5 h, and the total clearance was 393 ±110 and 427 ± 113 ml/min. Inactivation of saruplase in plasma was negligible.After 15 min, tcu-PA was detected in plasma. From the ratio of the areas under the curve of tcu-PA and total u-PA activities it was calculated that 28 ± 9.3% of the saruplase dose is converted into active tcu-PA. Systemic plasminaemia occurs as shown by a decrease in α2-antiplas-min and fibrinogen and an increase in fibrinogen degradation products. Thrombin-antithrombin complex formation indicated activation of the clotting system.Saruplase is eliminated rapidly from plasma in AMI patients. A variable, but significant proportion of saruplase is converted into active tcu-PA. At the end of the infusion tcu-PA accounted for 55% of total u-PA activity. Systemic plasmin generation and activation of the clotting system occur during saruplase treatment for AMI.